500 bead weaving patterns for bracelets - Ramon, Émilie (Stackpole Books, 2017)
"An encyclopedia of beaded bracelet patterns for your small loom. Weaving beaded bracelets on a small bead loom is easy, and with the 500 patterns in this book you can make all kinds of creative designs! From bold graphic prints to animals and flowers to retro or southwestern designs, there are plenty of patterns to suit your style. Each pattern shows how many and what color beads are needed and the placement of every bead so it's easy to complete any bracelet you choose."--